AB0681 The assessment of the cognitive and behavioural profiles in primary sjogren's syndrome. (23rd January 2014) - Davies, K.A.; Trimble, R.; Haynes, R.; Dowell, N.; Rusted, J.; Chan, D.
Abstract : Background: Sjogren's syndrome (SS) is a multi-system autoimmune disorder known to affect the CNS. Studies have reported that 7%>100% patients experience neuropsychological manifestations including cognitive impairment, depression and anxiety (1, 2). Depression has been shown to predict physician attendance and work status in SS (3). The relationship between cognitive and behavioural dysfunction is yet to be established in this disease group. Objectives: To determine the relationship between self- reported cognitive symptoms and measures of depression and anxiety in primary Sjogren's syndrome Methods: As part of an ongoing cognitive and quantitative neuroimaging study in 30 Sjogren's syndrome patients and 20 matched healthy controls, data on subjective cognitive dysfunction and measures of anxiety and depression have been collected in 27 primary SS patients and 14 age-, sex- and education-matched controls. Presence and severity of anxiety and depression was assessed using the self-administered Hospital Anxiety and Depression Scale (HADS). Self-reported cognitive symptoms, including failures in memory, perception and motor lapses were assessed using the Cognitive Failures Questionnaire (CFQ). Correlation between these variables was measured using two-tailed Pearson coefficient calculation. Results: Mean total HADS values for the SS and control group were 16.54 (95% confidence interval (CI) 13.67 to 19.41)and 8.29 (95% confidence interval 5.09 to 11.49) respectively. On the subscales for anxiety and depression, the mean depression score for patients was 6.78 (95% CI 5.09-8.52) and controls was 2.50 (95% CI 1.13-3.87). The mean anxiety score was 9.74 (95% CI 8.21-11.27) and 5.79 (95% CI 3.58-8) respectively. 44% (12/27) of patients and 7% (1/14) of controls had abnormal anxiety scores. 14% (4/27) of patients had abnormal depression scores whereas only one control had a borderline score. Bivariate correlation analysis revealed significant correlation between total cognitive failures score and total HAD, anxiety and depression subscale scores in the patient group (r=0.70, 0.62, 0.56 respectively, p=0.01) but not in the control group. Conclusions: Primary SS patients report a significantly increased level of subjective cognitive failure symptoms as assessed by the CFQ as well as significantly increased anxiety and depression measures. In keeping with previous study of subjective cognitive evaluation in affective disorders, the total CFQ score correlated with anxiety and depression scores in our patient group. While the increased reporting of cognitive failures in our patient group may relate to significantly increased affective disturbances, ongoing studies of objective cognitive test scores and biological correlates are necessary to explore the exact nature of this relationship. References: Soliotis, F.C., C.P. Mavragani, and H.M. Moutsopoulos, Central nervous system involvement in Sjogren's syndrome. Ann Rheum Dis, 2004. 63(6): p. 616-20. Valtysdottir, S.T., et al., Psychological well-being in patients with primary Sjogren's syndrome. Clin Exp Rheumatol, 2000. 18(5): p. 597-600. Westhoff, G., T. Dorner, and A. Zink, Fatigue and depression predict physician visits and work disability in women with primary Sjogren's syndrome: results from a cohort study. Rheumatology (Oxford), 2011. Disclosure of Interest: K. Davies: None Declared, R. Trimble Grant/Research support from: Funded by the Headley Trust, Sainsbury's Family Charitable Trusts, R. Haynes: None Declared, N. Dowell: None Declared, J. Rusted: None Declared, D. Chan: None Declared